1995
DOI: 10.1007/bf00020460
|View full text |Cite
|
Sign up to set email alerts
|

Production of biologically active hirudin in plant seeds using oleosin partitioning

Abstract: A plant oleosin was used as a 'carrier' for the production of the leech anticoagulant protein, hirudin (variant 2). The oleosin-hirudin fusion protein was expressed and accumulated in seeds. Seed-specific expression of the oleosin-hirudin fusion mRNA was directed via an Arabidopsis oleosin promoter. The fusion protein was correctly targeted to the oil body membrane and separated from the majority of other seed proteins by flotation centrifugation. Recombinant hirudin was localized to the surface of oil bodies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
72
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(72 citation statements)
references
References 41 publications
0
72
0
Order By: Relevance
“…It is likely that membrane topology and the hydrophobicity of the H domain favors transition into a region of oil in the ER membrane from which oil body formation can occur (18 -20). Oleosins are also used as carriers for recombinant protein production in seeds (21,22). Thus, the topology of this protein has a significant impact on the potential uses of oleosin-based production systems.…”
mentioning
confidence: 99%
“…It is likely that membrane topology and the hydrophobicity of the H domain favors transition into a region of oil in the ER membrane from which oil body formation can occur (18 -20). Oleosins are also used as carriers for recombinant protein production in seeds (21,22). Thus, the topology of this protein has a significant impact on the potential uses of oleosin-based production systems.…”
mentioning
confidence: 99%
“…Recently, many biopharmaceutical researchers have been actively developing vaccines and therapeutic proteins utilizing transgenic plants (Kumagai et al 1993, Parmenter et al 1995, Dieryck et al 1997, Tacket and Mason 1999. In this study, we demonstrated that IFN, a biologically active human protein could be obtained in a stable manner from cultivated calli using a simple inorganic liquid medium.…”
Section: Discussionmentioning
confidence: 72%
“…Recently, many biopharmaceutical investigators have begun to actively develop vaccines and therapeutic proteins utilizing transgenic plants (Kumagai et al 1993;Parmenter et al 1995;Dieryck et al 1997;Tacket and Mason 1999;Ma et al 2005). Considering the applications for oral administration and immunization, cereals such as rice will be utilized to produce these proteins.…”
Section: Discussionmentioning
confidence: 99%